ІНТЕГРАЦІЙНА ОСНОВА ОБРАЗОТВОРЧОЇ ПІДГОТОВКИ МАЙБУТНІХ АРХІТЕКТОРІВ (Педагогіка вищої та середньої школи, 2009)
The article discusses the integration aspects of fine art training of future architects, set directions and ways to integrate the learning process, outlined the main provisions of the technical system of integrated composite concepts.